The Stigmatized Vernacular : Where Reflexivity Meets Untellability - Shuman, Amy, 1951-; Goldstein, Diane E. (Book collections on Project MUSE., 2016)
As part of this multilayered conversation about stigma, this volume discusses the relationship between the stigmatized individual and our role as researchers. Here we address our own perspectives as researchers struggling with stigma issues and tellability, as well as scholarly reflexive concerns dealing with what can't be said when working with stigmatized groups or topics. The disciplinary focus of folklore positions us well to concentrate on the vernacular experience of the stigmatized, but it also propels us toward analysis of the performance of stigma, the process of stigmatization, and the political representation of stigmatized populations. These perspectives come to the fore in this book, as does the multilayered nature of stigma - its ability to reproduce, overlap, and spread, not just in terms of replication but also in terms of the ethnographer's ability to apprehend it and her ability to research and write about it.